Three decades after Bhopal: What we have learned about effectively managing process safety risks. Issue 4 (29th October 2015) - Vaughen, Bruce K.
Abstract : While no industrial chemical incident has had the magnitude for loss of life that occurred in 1984 at Bhopal, process safety incidents continue to occur today often resulting in serious injuries, fatalities, environmental harm, property damage, and business interruption. Over the last three decades, we have learned that these three interrelated foundations are essential for effective process safety programs: (1) process safety culture and leadership, (2) operational discipline, and (3) process safety systems. If any one of these foundations is weak, process safety incidents will occur and the organization's process safety performance will be poor. This article explores how the process safety systems are essential barriers when reducing risks, applying the layer of protection model and the bow tie barrier analysis model into a novel visual tool that can be used to identify both the foundational gaps and the process safety systems which failed. Although the Bhopal incident is used as the case study, the objective of this article is to provide a tool for others to use when summarizing their investigations in a way that helps them visually depict the investigation's findings and helps them prioritize and address weaknesses in one or more of their process safety program foundations. © 2015 American Institute of Chemical Engineers Process Saf Prog 34: 345–354, 2015